ANALISIS KAJIAN LOYALITAS PEGAWAI PT BRI CABANG PANDEGLANG UNIT PASAR TIMUR - Damayanti, Shinta; Saefullah, Encep; Putra, Arta Rusidarma (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This research is motivated by the employee loyalty of PT BRI Pandeglang Branch Pasar Timur Unit. Employee loyalty is a strategic element in maintaining organizational performance. This study aims to analyze employee loyalty at PT BRI Pandeglang Branch Pasar Timur Unit. Reviewed from 4 indicators: 1) Obedience or Compliance, 2) Responsible, 3) Devotion, and 4) Honesty.Methods: The qualitative approach uses phenomenological methods, obtained through observation, documentation, triangulation, and interview techniques. Informants are divided into three levels: top, middle, and bottom.Results: The results of the study show that: 1) Employee compliance or obedience shows that employees have an awareness of compliance and commitment to professionalism; 2) Employee responsibility shows that employee responsibility is reflected through loyalty in completing tasks, even in the midst of a high workload; 3) employee dedication shows that loyalty to long-term career development and willingness to take initiatives outside of formal duties; and 4) employee honesty shows that loyalty to honesty, both in reporting work and admitting mistakes, but fear of stigma and punishment are factors that inhibit complete openness. Keywords: Bank, Employee, Loyalty